THE CORRELATION BETWEEN THE AUTHORITATIVE PARENTING OF ELEMENTARY SCHOOL TEACHER PARENTS AND LEARNING ASSISTANCE FOR CHILDREN IN SUKOHARJO REGENCY - Kurniadi, Kurniadi; Purnasari, Nurwulan (UIN Sunan Kalijaga Yogyakarta, 2023)
Most parents face difficulties in learning assistance at home that make children unable to learn anything. This study aimed to ascertain the relationship between the authoritative parenting of elementary school teacher parents and learning assistance for children in Sukoharjo Regency. The validity test, reliability test, normality test, homogeneity test, linearity test, and basic linear regression analysis were the ex post facto quantitative techniques used in this research. Cluster sampling resulting in 317 participants in Sukoharjo was utilized to select the study samples out of a population of 6,175 elementary school teachers. The findings revealed a substantial correlation between the learning assistance for elementary school students in Sukoharjo and the authoritative parenting style of elementary school teacher parents. The straightforward linear regression test showed that 0.000 to 0.05 was a significant level. In addition, it was found that Y = 28.174 + 0.413X was a positive regression equation. These findings indicate a substantial association between the learning assistance variable and authoritative parenting characteristics.